Rancang Bangun Web Profile Khayangan Bakery Untuk Memperluas Wawasan Kuliner Wilayah Kendal - Pradapa, Sri Yulianto Fajar; Maskur, Ali; Listiyono, Hersatoto; Daniswara, Alfreda Khansa (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
This article discusses the design and development of a profile website for Khayangan Bakery, a bakery located in the Kendal region of Central Java. The purpose of developing this website is to expand the culinary awareness of the people in Kendal and its surroundings regarding the bread and cake products offered by Khayangan Bakery. The website is designed with consideration for users' needs for easy and quick access to information, as well as to strengthen Khayangan Bakery's brand image in the digital world. The methods used in the development include requirements analysis, user interface (UI) design, front-end and back-end development, and functionality testing. The result of this development is a responsive, informative, and user-friendly website, which is expected to enhance Khayangan Bakery's competitiveness and attract more customers from both Kendal and its surrounding areas.